2018
DOI: 10.1177/1461444818768259
|View full text |Cite
|
Sign up to set email alerts
|

The social mediated age of information: Twitter and Instagram as tools for information dissemination in higher education

Abstract: Despite high levels of global connectivity, Americans are generally underinformed about the world. The US Department of Education named social media as a viable option for improving learning objectives, yet minimal research supports such a claim regarding internationalization. While what research exists exclusively investigated Facebook, no research explored the viability of other popular platforms, such as Twitter or Instagram. Through an experimental design conducted on 405 college students, this study probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…A few studies have explored Instagram use by students as a required part of coursework (e.g., Arceneaux & Dinu, 2018 ; Erarslan, 2019 ). Also, Instagram use for informal educational purposes in the medical education field has received some attention, primarily related to the platform’s visual affordances for medical specialties such as anatomy and dentistry ( Douglas et al., 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few studies have explored Instagram use by students as a required part of coursework (e.g., Arceneaux & Dinu, 2018 ; Erarslan, 2019 ). Also, Instagram use for informal educational purposes in the medical education field has received some attention, primarily related to the platform’s visual affordances for medical specialties such as anatomy and dentistry ( Douglas et al., 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the digital media ecosystem, social networks have acquired great social relevance [ 11 ], joining traditional socializing agents (family, school, peer groups and communication media) in information processes and identity construction [ 12 , 13 ]. Twitter has become one of the most used social networks as a news media by stakeholders [ 14 , 15 ] as well as by journalists [ 16 , 17 ], and of course by its users [ 18 ], being employed by very diverse audiences to get information on news events [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that visual products are more efficient in capturing the publics attention (Arceneaux & Dinu, 2018). Thus, incorporating technologies and finding innovative ways to share knowledge, like the videos analyzed here, are essential for strengthening the learning process (Agama et al, 2017).…”
Section: Discussionmentioning
confidence: 94%